Comparative Implementation of the 2013 Curriculum and the Merdeka Curriculum in State Junior High Schools - Wulandari, Dwi; Ali Mustofa, Triono (Tadrib: Jurnal Pendidikan Agama Islam, 2023)
This study aims to understand the differences between the independent curriculum and the 2013 curriculum, to compare the independent curriculum and the 2013 curriculum at the junior high school level, and to analyze some of the difficulties experienced in implementing the 2013 curriculum and the independent curriculum at SMP Negeri 1 Bringin. This research uses qualitative research methods with observation and interview data collection techniques. The subject of this research is the Vice Principal for Curriculum, Mrs. Tri Retnaningtyas, S.Pd. The results of the research show that the 2013 curriculum has a fairly good concept in every educational process. however, the application of the independent curriculum in some driving schools is carried out in the first year with a fairly good implementation. which has been developed in various schools this year. some schools are still carrying out a design agenda related to formulas that are in accordance with the implementation of the independent curriculum concept. poisonous in the description that has been mentioned, the application of the Easter independent curriculum is carried out in an analysis that is better and quite in accordance with the existing educational culture in Indonesia compared to the 2013 curriculum. Therefore, there are some things that must be taken into consideration by a policymaker as well as an implementer in the world of education, where the Merdeka curriculum can be applied in a targeted manner or improve some of the previously implemented curricula. not just a program whose implementation is carried out by force in all education or junior high schools in Indonesia, especially those in Ngawi Regency.